2018
DOI: 10.1080/03639045.2018.1438467
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-made pH-sensitive polyacrylic acid functionalized mesoporous silica nanoparticles for efficient and controlled delivery of anti-cancer drug Etoposide

Abstract: A multifaceted therapeutic platform has been proposed for controlled delivery of Etoposide (ETS) leading to a synergistic advantage of maximum therapeutic efficacy and diminished toxicity. A state of the art pH responsive nanoparticles (NPs) MSNs-PAA consisting of mesoporous silica nanoparticles core and polymeric shell layers, were developed for controlled release of model anti-cancer drug ETS. Graft onto strategy was employed and amination served as an interim step, laying a vital foundation for functionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…WAXRD patterns were recorded to determine the crystalline nature of ETE (Figure 3(II)). Sharp peaks were observed at theta values of 10.9, 16.5, 19.9, 21.3, 24.1 and 25.9 [16]. For ETE loaded MSNs absence of crystalline phase was observed.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 91%
See 2 more Smart Citations
“…WAXRD patterns were recorded to determine the crystalline nature of ETE (Figure 3(II)). Sharp peaks were observed at theta values of 10.9, 16.5, 19.9, 21.3, 24.1 and 25.9 [16]. For ETE loaded MSNs absence of crystalline phase was observed.…”
Section: X-ray Diffraction Studiesmentioning
confidence: 91%
“…MCM-41 mesoporous silica nanoparticles were synthesized based on template synthesis method with few alterations [15,16]. For the fabrication of MSNs, 2.21 grams (g) of CTAB playing a role of the structural template was dissolved in deionized water and blended for 5 min (min).…”
Section: Preparation Of Mesoporous Silica Nanoparticles and Chemical mentioning
confidence: 99%
See 1 more Smart Citation
“…[26] Recently, Saroj and Rajput have shown that Etoposide encapsulated poly(acrylic acid)-mesoporous silica nanoparticles have more therapeutic potential than the free drug on prostate cancer cells. [27] Inorganic nanoparticles which offer an imaging modality are also very popular since they allow the combination of imaging with therapy. Superparamagnetic iron oxide nanoparticles (SPION) are the most popular of such nanoparticles, since they are already used in the clinic as MRI contrast agents.…”
Section: Introductionmentioning
confidence: 99%
“…Water-soluble pH-responsive polymers, labeled covalently with fluorescent dyes, have attracted a major focus of interest in polymer photophysics due to their stimuli-responsive self-organizing behavior [1][2][3]. They have revealed numerous important applications for surface modification, structuring and, in particular, rheology control [1].…”
Section: Introductionmentioning
confidence: 99%